PEMBERDAYAAN MASYARAKAT MANDIRI PERKOTAAN (Suatu Studi di Kelurahan Matali Kecamatan Kotamobagu Timur Kota Kotamobagu) - ISTYKHOMAH, RETNO - (Sam Ratulangi University, 2014)
Abstract: Poverty in Indonesia is an evidence and also as a valuable lesson that top-down policies is not good absolutely for the Indonesia people . Everything which is not open forcreativities will influence in high dependency , creating weakness and, blunting creativity .National Program for Community Empowerment comes as a solution from thegovernment to empower communities by maximizing and optimizing capital - social capital in the community such as mutual cooperation , togetherness , solidarity , and cooperation as the cornerstone of any poverty alleviation program that will be implemented .In this case , the PNPM believes that a more effective approach to realize the process of behavioral change is through a community empowerment approach and strengthening the role of local government in appreciating and supporting the independence of its people . Empowerment process is done by constantly striving to develop a critical awareness of the community towards universal human values , social principles and the principles of sustainable development as a solid foundation to build an independent and prosperous society . The learning process takes place at the community level during the program and post- program by the community itself by building and institutionalizing District LearningCommunity (DLC).Keyword : poverty , PNPM Mandiri , process .